Protective effects of curcumin on antioxidant status, body weight gain, and reproductive parameters in male rats exposed to subchronic 2,3,7,8-tetrachlorodibenzo-p-dioxin - Gülcü Bulmuş, F; Sakin, F; Türk, G; Sönmez, M; Servi, K (My University, 2013)
The aim of this study was to investigate the effects of curcumin (CUR) on antioxidant status, body weight (BW) gains, and some reproductive parameters in male rats exposed to subchronic doses of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). Thirtytwo rats were divided into four groups. The first group was kept as control. The second group (TCDD group) was given TCDD at a dose of 50 ng kg 1 BW per day; the third group (CUR group) was treated with CUR at a dose of 80 mg kg 1 BW per day. The fourth group (TCDD ? CUR group) was given TCDD and CUR at the same doses simultaneously. Malondialdehyde (MDA) levels were significantly increased in the TCDD group. In addition, TCDD exposure decreased liver superoxide dismutase (SOD) activity, catalase (CAT) activities of kidney and brain, glutathione peroxidase (GSH-Px) activities of liver, kidney, and brain, and glutathione levels of liver, kidney, and heart. However, CUR treatment with TCDD exposure decreased MDA levels in all tissues and increased SOD activities of liver, kidney, and brain, CAT activity of heart, and GSH-Px activities of heart and brain. TCDD caused a decrease in BW gain, and CUR partially eliminated this effect of TCDD. In addition, while reproductive organ weights, sperm concentration, and sperm motility tended to decrease with TCDD exposure, these effects tended to be close to normal levels by CUR treatment. In conclusion, CUR was seen to be effective in the treatment and prevention of toxicity induced by subchronic TCDD exposure.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: curcumin 2; 3; 7; 8-tetrachlorodibenzo-p-dioxin antioxidant status body weight gain reproductive parameters